Rural water supply systems in Nepal: factors affecting equitable access to water - Raut, M.; Rajouria, Alok (Southasia Institute of Advanced Studies (SIAS), 2022)
Equity in rural water supply systems has been a major concern of users, policymakers, and practitioners in Nepal. Communities continue to face persistent inequities in access to safe water amid the changing livelihood environment due to migration, the transition to federalism, and entrenched social hierarchies. In this situation, increasing competition for water, a resource that continues to diminish due to natural and anthropogenic causes, has aggravated disparities in access. It is usually the poor and marginalised groups who are disproportionately affected. The long-standing factors hindering equitable access to an adequate water supply amidst the COVID-19 pandemic when water is necessary for handwashing needs a sustainable resolution. Based on the learnings of a three-year research project that aimed to understand the role of gender and power dynamics in the functionality of community water systems, this paper provides insights into collective water management practices and equity amidst the pandemic. Evidence from the study shows deficiencies in community institutions created for inclusive and sustainable management of local water sources. The paper argues that achieving gender and social inclusion in community water management requires going beyond the implementation of prescribed quotas for women and under represented minority groups. Our learnings from the COVID-19 pandemic highlight the importance of equitable access to safe water and emphasise how low-income households are at higher risk of contracting the virus through shared water infrastructures. A household survey, together with a mix of qualitative methods, were the primary sources of data. Based on data from the case study sites—Ward No. 8, Gurans Rural Municipality, Dailekh district and Ward No. 6, Chandranagar Rural Municipality, Sarlahi district—we conclude that changing socio-economic contexts, prevailing social norms and practices, and premature and frequent infrastructure breakdown are barriers to fair and equitable access to water, and that local governments’ enhanced authority is a new opportunity.